Risk factors of patellofemoral instability in patients with hypermobile Ehlers-Danlos syndrome - Schmidt, Sebastian; Leite, Chilan Bou Ghosson; Bumberger, Alexander; Franco, Domenico; Jacobs, Cale Andrew; Lattermann, Christian (Archives of orthopaedic and trauma surgery, 2025)
Hypermobile Ehlers-Danlos Syndrome (hEDS) is a connective tissue disorder characterized by joint hypermobility and ligamentous laxity, leading to a high prevalence of patellar instability. While anatomical risk factors for patellar dislocation (PD) have been extensively studied in the general population, their specific role in hEDS remains unclear. This study aimed to evaluate anatomical predictors of patellar dislocation in patients with hEDS by comparing individuals with and without PD.
Online veröffentlicht: 11. August 2025
Gesehen am 06.11.2025